Formulation and Evaluation of Cefixime Strips for Chronic Periodontal Treatment - Parmar, Mr. Rakeshkumar (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To develop a periodontal pocket drug delivery system of cefixime loaded ethyl cellulose (EC) strips using hydroxypropyl cellulose (HPC), hydroxypropylmethyl cellulose K4M (HPMC K4M), and Eudragit RL-100 as copolymers with different concentrations. Materials and Methods: Casting/solvent technique was utilized to prepared strips. The prepared strips were evaluated for physicochemical parameters such as Fourier transform infrared spectroscopy (FT-IR), thickness, folding endurance, percentage moisture loss, content uniformity, in-vitro drug release, and in-vitro antibacterial activity. Results and Discussion: FT-IR data showed that drug and excipients were compatible with each other. The formulated strips were flexible, having uniform drug content, and exhibited acceptable physicochemical characteristics. The drug release was sustained for up to 5 days, even if the strips demonstrated initial burst effect. As formulation P3 showed better drug release profile, was optimized among all other formulations. Conclusion: The present work proposes that the sustained release cefixime loaded EC strips with copolymer HPMC K4M have a significant role in the treatment of chronic periodontitis.